Editorial - Grilli, Matteo (Southern Journal for Contemporary History, 2024)
One of the topical subjects globally at present is migration. From refugees fleeing wars in Ukraine and Russia to Donald Trump’s electioneering on immigration and border control in the United States of America to allegations of xenophobia against immigrants in Southern Africa, the subject remains alive. Historians have long researched and written on the topic, showing as they do, various facets to the subject. Even in the current discourses, historians remain attracted to the topic as is evidenced in this journal. This issue of the Southern Journal for Contemporary History opens with an article by Anusa Daimon entitled “Prominent Malawian Machona Progenies in Zimbabwe”. The article deals with a very important topic: the role of immigrants in colonial and post-colonial African territories. The presence of Malawians in Zimbabwe originated from the colonial labour migration system. Over the decades, as evidenced by Daimon, Malawians have carved significant roles in Zimbabwe and the whole southern African region. Brian Maregedze and Thembani Dube’s article “The involvement of Congolese and Rwandese immigrants in Harare urban transport sector, 1993-2022” also deals with African immigrants in Zimbabwe. Similarly to Daimon’s contribution, it also includes an important use of oral sources. Tola Odubajo’s contribution deals with ECOWAS’ response to the 2021 Guinean coup d’etat. This is a welcomed topic for a journal that aims to cover areas of the continent beyond the English-speaking African territories, to which it mainly caters, and which encourages analyses of contemporary African political issues. We hope to see more contributions covering themes on Francophone and Lusophone Africa, as well as North Africa, in the future.